Transmissão transplacentária do Papilomavírus humano - Rombaldi, Renato Luis (My University, 2014)
Genital infection by the human Papillomavirus is one of the most frequent sexually transmitted diseases, and about 40 genotypes were detected in female and male anogenital region. The aim of this study was to evaluate the diagnostic efficiency of the colletction methods by brush and PCR, peniscopy and histology for HPV diagnosis of the human Papillomavirus in clinical and subclinical penis infections, as well as to determine epidemiologic contaminated profile male population. A prospective study was carried out in men seeking for treatment at the urology service due to lesion in the penis, as well as in men whose sexual partners are women with either serious or mild lesions in the uterine cervix. The patients have been subjected to epidemiologic interview, peniscopy and to sample collection by brush and biopsy. The collection of methods by brush and PCR, peniscopy and histology, used for the diagnosis of HPV infection, have been assessed in terms of their sensitivity, their specificity and also regarding the ratio between their positive and negative probability. Of the 80 men included in study, 38 (47.5%) were negative for the HPV/DNA, whereas 42 (52.5%) were positive to HPV/DNA, out of whom 29 (36.2%) had clinical infection, 12 (15%) had subclinical infection and one (1.3%) had a latent infection. The performance standards of the diagnostic methods for clinical HPV infection was considered excellent for brush and PCR, histology and peniscopy + histology; brush + PCR were the methods that showed the best performance when used alone for the diagnosis of subclinical HPV infection. The epidemiologic analysis showed an mean age 28,1+9,6 years for HPV/DNA positive group, with a clear prevalence of this infection in people with less age of 29 old. There were significant difference between HPV infection and the following variables: age, marital status-single, first sexual intercourse before 16 old and number of sexual partners in the last 2 or more years.
A infecção genital pelo Papilomavírus humano é uma das doenças sexualmente transmissíveis de maior freqüência, sendo que cerca de 40 genótipos foram detectados na região anogenital feminina e masculina. Este estudo visou avaliar a eficácia diagnóstica dos métodos coleta de material com escova e PCR, peniscopia e histologia, para diagnóstico do Papilomavírus humano em infecções clínicas e subclínicas de pênis, bem como estabelecer o perfil epidemiológico da população masculina contaminada. Para tanto, desenvolveu-se um estudo prospectivo em homens que procuraram o serviço de urologia com lesão no pênis, e em homens parceiros sexuais de mulheres portadoras de lesões de baixo ou alto grau do colo uterino. Os pacientes foram submetidos à entrevista epidemiológica, peniscopia e coleta das amostras com escova e por biopsia. Avaliou-se a sensibilidade, a especificidade e a razão de probabilidade positivo e negativo dos métodos coleta com escova e PCR, peniscopia e histologia para diagnóstico da infecção pelo HPV. Dos 80 homens estudados, 38 (47,5%) apresentaram-se negativos para HPV/DNA e 42 (52,5%) apresentaram-se positivos para HPV/DNA, dos quais 29 (36,2%) eram portadores de infecção clínica, 12 (15%) eram portadores de infecção subclínica, e um (1,3%) era portador de infecção latente. As medidas de desempenho dos métodos diagnósticos da infecção clínica pelo HPV foram consideradas muito boas para os métodos coleta de material com escova e PCR, histologia e peniscopia + histologia; e a coleta de material com escova e PCR foram os métodos que apresentaram o melhor desempenho, quando empregados isoladamente, para diagnóstico da infecção subclínica pelo HPV. O estudo epidemiológico evidenciou média de idade do grupo HPV/DNA positivo de 28,19,6 anos, com clara prevalência dessa infecção abaixo de 29 anos. Houve associação estatística entre as variáveis, média de idade, estado marital solteiro, idade da primeira relação sexual 16 anos, número de parceiras ≥2 no último ano e infecção pelo HPV.
Keywords: Papilomavírus; Doenças virais - Transmissão transplacentária